2018
DOI: 10.1007/s11250-018-1570-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of subclinical mastitis on the concentration of immunoglobulins A, G, and M, total antioxidant capacity, zinc, iron, total proteins, and calcium in she-camel blood in relation with pathogens present in the udder

Abstract: The present study aims to evaluate the amount of immunoglobulins A, G, and M in she-camel blood serum in relation with the presence of pathogens in the udder, and to compare the antioxidative capacity and the concentration of zinc, iron, total proteins, and calcium. Milk and blood samples from she-camels from south Jordan were taken; according to milk bacteriological examination, the animals were divided into two groups: (Gm) which contained samples of milk contaminated with bacteria and (Gh) which contained u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…The serum IgG concentrations were significantly elevated in the high SCC animals compared the low SCC animals in both the Waddah and Majaheem groups. Our observations were not different from previous studies indicating increased immunoglobulins secretion in lactating animals with subclinical mastitis (Lehmann et al 2015;Hayajneh et al 2018). A study by Lehmann et al (2015) reported a positive association between SCC numbers and IgG levels and that the IgG levels could be used as a parameter to differentiate between low and high SCC milk samples.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The serum IgG concentrations were significantly elevated in the high SCC animals compared the low SCC animals in both the Waddah and Majaheem groups. Our observations were not different from previous studies indicating increased immunoglobulins secretion in lactating animals with subclinical mastitis (Lehmann et al 2015;Hayajneh et al 2018). A study by Lehmann et al (2015) reported a positive association between SCC numbers and IgG levels and that the IgG levels could be used as a parameter to differentiate between low and high SCC milk samples.…”
Section: Discussioncontrasting
confidence: 61%
“…A study by Lehmann et al (2015) reported a positive association between SCC numbers and IgG levels and that the IgG levels could be used as a parameter to differentiate between low and high SCC milk samples. Hayajneh et al (2018) reported significant increases in the concentrations of serum immunoglobulins A, G, and M in relation to subclinical mastitis in camels. Another study by Musayeva et al (2016) has also indicated significant increases in the IgG levels in cows' milk samples with SCC ranging from 201,000 to ≥401,000 cells/mL compared to milk samples with ≤200,000 cells/mL.…”
Section: Discussionmentioning
confidence: 94%
“…LPO is a non-immunoglobulin protective glycoprotein that is present in milk and other human and animal fluids (Hao et al 2019). It is believed that the LPO plays a crucial role in the host's innate defense system (Hayajneh 2018). The LPO can affect both Gram-positive and Gram-negative bacteria to varying degrees, and antiviral effects have also been observed (Hu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…and vitamins such as vitamin A, E and C should be provided to animals [4,9,56]. These minerals and vitamins possess antioxidant and immunity modulating properties favorable for animals which helps them in fighting against mastitis cases [57][58][59][60][61][62][63][64].…”
Section: Nutritional Management Of Animalsmentioning
confidence: 99%